2002
DOI: 10.1063/1.1481773
|View full text |Cite
|
Sign up to set email alerts
|

Microwave mixing in microbridges made from YBa2Cu3O7−x thin films

Abstract: We present a systematic study of the response of a YBa 2 Cu 3 O 7Ϫx thin-film microbridge to millimeter wave radiation. The dependencies of the microwave response spectrum on the bias voltage and operating temperature have been measured on samples made from YBa 2 Cu 3 O 7Ϫx films with different thicknesses. Once the bias voltage exceeds the value corresponding to the first maximum of differential resistance, the value of the Ϫ3 dB roll-off frequency of the microbridge response is drastically reduced. On the ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…At low temperatures the penetration and movement of magnetic vortices can modify the current carrying ability of thin films of superconductors of the second type and the performance of devices made from these films. It has been found that the hot-electron bolometer (HEB) mixers made from low- [9] and high-T C [10] superconducting thin films demonstrate an increase of the intermediate frequency bandwidth at subTHz local oscillator frequency due to oscillations of the magnetic vortices. Nucleation and movement of the vortices is currently considered as a mechanism responsible for the generation of dark counts in the superconducting nanowire single-photon detectors (SNSPD) [11].…”
Section: Introductionmentioning
confidence: 99%
“…At low temperatures the penetration and movement of magnetic vortices can modify the current carrying ability of thin films of superconductors of the second type and the performance of devices made from these films. It has been found that the hot-electron bolometer (HEB) mixers made from low- [9] and high-T C [10] superconducting thin films demonstrate an increase of the intermediate frequency bandwidth at subTHz local oscillator frequency due to oscillations of the magnetic vortices. Nucleation and movement of the vortices is currently considered as a mechanism responsible for the generation of dark counts in the superconducting nanowire single-photon detectors (SNSPD) [11].…”
Section: Introductionmentioning
confidence: 99%
“…For YBCO film thicknesses above 30 nm T c is nearly constant and well above 77 K. For films thinner than 30 nm T c decreases significantly. This can be explained by the above-mentioned lattice mismatch leading to oxygen deficiency in the YBCO film, which results in a reduction of T c [13] down to 25 K for 15 nm thick films. The T c of films with d < 30 nm has been improved by a decrease of the CeO 2 layer thickness.…”
Section: Ybco Thin-film Microbridge Detectormentioning
confidence: 94%
“…Besides, YBCO was attractive in several respects, e.g., operating temperature with light cryogenics, or fast response, due to its very short electron-phonon relaxation time τ ep , in the ps range [6][7][8]. Early YBCO HEB mixers were demonstrated at mm-wave [9][10][11][12] or THz [9,10,[13][14][15] frequencies. Difficulties were encountered, however, which mainly arose from YBCO chemical reactivity to atmospheric water and carbon dioxide and to the fabrication process as well, which compromised the durability of good performances for frequency mixing operation [16].…”
Section: Introductionmentioning
confidence: 99%
“…Difficulties were encountered, however, which mainly arose from YBCO chemical reactivity to atmospheric water and carbon dioxide and to the fabrication process as well, which compromised the durability of good performances for frequency mixing operation [16]. They also arose from the superconducting film to substrate phonon escape time τ esc , much longer for YBCO [17] than for Nb, for instance [18], with a detrimental effect on the instantaneous much longer for YBCO [17] than for Nb, for instance [18], with a detrimental effect on the instantaneous bandwidth [11][12][13]19]. More recently, MgB 2 has met a sustained interest as a compromise between NbN and YBCO, in terms of operating temperature, but also in terms of instantaneous bandwidth [20,21].…”
Section: Introductionmentioning
confidence: 99%